Why Europe Needs a Public Investment Plan - Mario Pianta (Intereconomics, 2016)
In the continuing stagnation of European economies, the persistence of inadequate demand plays a crucial role that deserves greater attention. First and foremost, we are in a context of slower international growth, in which global world trade is growing more slowly than global GDP. This implies that exports are not in the position to be the driver of renewed growth for Europe.
Keywords: 330